ISOLASI BAKTERI PENGHASIL ENZIM PROTEASE BACILLUS THURINGIENSIS IRODI PADA ONCOM MERAH PASCA FERMENTASI 24 JAM - Radna Safitri; Sakti Imam Muchlissin; Ana Hidayati Mukaromah; Sri Darmawati; Stalis Norma Ethica (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The need for protease enzymes in Indonesia and the world continues to increase, requiring  new  protease  sources.  Bacteria  are  beneficial  sources  of  protease because they are easy to obtain and rapidly multiply. Bacterial identification could be done molecularly through analysis of the 16S rRNA gene. This study aimed to obtain an isolate of protease-producing bacterium from 24-h post-fermented red oncom and to identify the obtained bacterial strain molecularly by 16S rRNA gene sequence. The protease production test on bacteria found in red oncom sample was done  using  a  selective  medium,  Skim  Milk  Agar  (SMA).  DNA  genomes  of proteolytic bacterial cells were extracted by Promega KIT. The amplifying process of 16S rRNA gene using the Polymerase Chain Reaction (PCR) method. The amplified  DNA  were  analyzed  using  the  BLAST  program.  The  results  of  the research found 8 isolate of bacterias. The most unique isolate was IROD1.3. It has significant  proteolytic  activity  based  on  the  ability  to  produce  clear  zone  of protease on SMA medium with a diameter of 85,00 mm. Isolate IROD1.3 was identified  molecularly  as  Bacillus  thuringiensis  with  similarity  of  96% to  the sequence of 16S rRNA gene Bacillus thuringiensis strain TERI SID4 (Genbank access code: KX822158.1). Keywords: Protease, 16S ribosomal RNA gene, red oncom, proteolytic bacterium